Corruption in the public sector : an international perspective - Krishna K. Tummala (Emerald Publishing Limited, 2021)
This edited collection examines corruption in the public sector, assessing case studies from across the globe in order to provide an international perspective on this worldwide issue. Case studies include an examination of how corruption has been minimized in Singapore and Hong Kong; an assessment of corruption in India under Modi, who was elected on a promise to reduce corruption; a study of corruption in Bangladesh, and an evaluation of attempts to curb corruption in South Africa. This collection also includes a comparative study of corruption in Brazil and Chile, and a global perspective on the development of ethical privacy policies in e-government. The original case studies included in this book are brought together in an effort to identify common themes that impinge upon the fight against corruption, despite the particular nuances of individual nations. The contributions included in this edited collection also cover themes that are not often studied, including corruption in government procurement, the nascent issue of the 'right to privacy' stemming from e-governance, and the proclivity of governments to hide behind Official Secrets Acts to withhold information - ostensibly guaranteed under the 'right to information' which is vital in the fight against corruption. Providing a broad overview on public sector corruption, including local and national perspectives, this edited collection is essential reading for scholars of both public policy and corruption worldwide.
Includes index.
Keywords: Administrative agencies -- Corrupt practices.; Civil service ethics.; Political Science, Corruption & Misconduct.; Civil service & public sector.; elektronické knihy; electronic books